Pengaruh Budaya Kerja, Komitmen dan Komunikasi terhadap Kinerja Pegawai - Sudibyo, Priyo; Dasilva, Katharina Benedikta Sinta (University of Merdeka Malang, 2023)
This research was conducted to analyze the influence of work culture, commitment, and communication on employee performance at the Malang City Government Environmental Service. The researcher used a questionnaire with a total of 30 respondents who worked in the Malang City Government's Environmental Service. The analysis tool uses multiple regression analysis. Based on the results of the analysis, the performance of employees of the Malang City Government Environment Service is influenced by work culture, commitment, and communication. Aspects of work culture have the greatest influence on employee performance in the area of the Malang City Government Living Area Service.Keywords: Commitment, Communication, Employee Performance, Work Culture